Five-Year Sales Trends of Osteoporosis Medications in Korea: A Market Analysis Based on IMS Health Sales Audit Data (2018–2023) - Jung Yoon Park; Youn-Jee Chung; Mee-Ran Kim; Jae-Yen Song (Medicina)
Background and Objectives: Osteoporosis is a common chronic condition after menopause that increases the risk of fractures. In South Korea, the prevalence of osteoporosis among adults aged 50 and older is 22.4%, with 94.4% of treated patients being women, highlighting its significant impact on postmenopausal health. In this study, we examine the sales trends of osteoporosis medications in Korea from 2018 to 2023 to understand current usage patterns and market dynamics. Materials and Methods: This study is a retrospective analysis based on pre-recorded sales data from Intercontinental Marketing Services (IMS). Data covering a five-year period (2018–2023) were analyzed to examine the sales trends of osteoporosis medications, including bisphosphonates, selective estrogen receptor modulators (SERMs), parathyroid hormone analogs, denosumab, romosozumab, and others. Romosozumab, approved in November 2019, was included in the analysis. Given the nature of this study, no direct patient data or clinical interventions were involved. Results: The total market size for osteoporosis medications in South Korea reached USD 285.42 million in 2023, reflecting a 15.3% increase from 2022. Bisphosphonates, previously the dominant therapy, experienced an 11% decline in market share over five years. Meanwhile, denosumab, a receptor activator of the nuclear factor-κB ligand inhibitor, showed a remarkable growth rate of 957.6% from 2018 to 2023, surpassing bisphosphonates in their market share. Romosozumab, a newly introduced anabolic agent, accounted for 7.4% of the market, with sales increasing by 59% in 2023. Conclusions: This analysis revealed major shifts in treatment preferences, with newer drugs like denosumab and romosozumab gaining prominence over traditional bisphosphonates. These trends highlight the increasing clinical adoption of anabolic agents for high-risk patients and the impact of expanded reimbursement policies on osteoporosis management. Given the increasing use of advanced therapies, it is essential to monitor treatment access, patient adherence, and long-term clinical outcomes. Understanding these sales trends can aid healthcare professionals and policymakers in optimizing osteoporosis treatment strategies and ensuring better patient care.